Study on the role of TDRD9 rs2273841 with male infertility of Vietnamese - Thuy Duong, Nguyen; Duc Duy, La; Thu Ha, Duong (Vietnam Journal of Biotechnology, 2021)
Male infertility is a complex disease caused by multiple factors, including genetic ones. Among genes involved in spermatogenesis, TDRD9 has been demonstrated to play an important role in piRNA synthesis, but no association study between single nucleotide polymorphisms (SNPs) of TDRD9 and male infertility has been conducted to date. Therefore, this study focused on establishing the relationship between SNP TDRD9 rs2273841 and male infertility. Total DNAs were isolated from 324 Vietnamese individuals comprising 164 non-obstructive azoospermic and oligozoospermic patients and 160 healthy controls having at least one child. Genotypes of this polymorphism were determined using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). Chi-Square test was used to test whether allele distribution of TDRD9 rs2273841 follows Hardy-Weinberg Equilibrium (HWE). Chi-Square test or Fisher’s exact test was used to check three models (additive, recessive, dominant) for the association of rs2273841 with male infertility. The results indicated that TDRD9 rs2273841 followed Hardy-Weinberg equilibrium (p-value > 0.05) in the control group. However, no association between the polymorphism and male infertility was established in all three models (additive, dominant, and recessive) (p-value > 0.05). This study would provide a basis for further studies on the association of TDRD9 with male infertility in the Vietnamese population.